The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1103/physrevb.96.165206
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of polar distortion and metallicity in PbTi1xNbxO3

Abstract: Abstract:Ferroelectricity has been believed unable to coexist with metallicity since the free carriers can screen the internal coulomb interactions of dipoles. Very recently, one kind of materials called as ferroelectric metal was reexamined. Here, we report the coexistence of metallicity and polar distortion in a new candidate for ferroelectric metal PbTi1-xNbxO3 via doping engineering. The ferroelectric-like polar distortion in all the doped PbTi1-xNbxO3, with x ranging from 0.04 to 0.12, was confirmed by th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…In the diffusive regime, thermal conductivity does not change with a width. In contrast, thermal conductivity in the hydrodynamic regime increases superlinearly with a sample width 4,5,15,16 . In the ideal hydrodynamic regime where there is no U-scattering and a sample size is much larger than the there is no U-scattering.…”
Section: B Sample Width Dependence Of Thermal Conductivitymentioning
confidence: 96%
See 2 more Smart Citations
“…In the diffusive regime, thermal conductivity does not change with a width. In contrast, thermal conductivity in the hydrodynamic regime increases superlinearly with a sample width 4,5,15,16 . In the ideal hydrodynamic regime where there is no U-scattering and a sample size is much larger than the there is no U-scattering.…”
Section: B Sample Width Dependence Of Thermal Conductivitymentioning
confidence: 96%
“…For suspended graphene, it has not been discovered yet if graphene exhibits a temperature dependence of thermal conductivity that is significantly different from ballistic case so that the Poiseuille flow can be clearly observed in experiment. Recent studies qualitatively showed thermal conductivity of graphene that increases faster than ballistic limit 5,15,16 . However, they relied on a simplified Callaway's scattering model 17,18 and some of them 15,16 used an empirical relation for scattering rates that was developed for three-dimensional materials 19,20 , hindering quantitative guidance of future experimental efforts from first principles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More progress has been made lately with a study ( 6 ) reporting on the observation of polar domains and strain-induced ferroelastic switching in bulk polar metal Ca 3 Ru 2 O 7 at room temperature. Another strategy that has also been commonly used, besides investigating metallic systems with a noncentrosymmetric crystal structure ( 7 ), is to dope well-established ferroelectric materials, such as BaTiO 3-δ ( 8 , 9 ) and Nb-doped PbTiO 3 ( 10 ). However, the ferroelectric instability weakens with increasing electronic density in these systems and will eventually be destroyed above a certain critical density ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly located in the flexure belt in the west of Shanxi. The whole presents the trend of east high and west low [16][17][18]. According to the comparative observation of field outcrops and the drilling of exploration wells, the Carboniferous-Permian in the study area developed from bottom to top with Benxi Formation (C2b)-Taiyuan Formation (P1t)-Shanxi Formation (P1s)-Shihezi Formation (P2h) -Shi Qianfeng Group (P3sq).…”
Section: Geological Backgroundmentioning
confidence: 99%